Taxonomy of Agapostemon angelicus and the A. texanus species complex (Hymenoptera, Halictidae) in the United States - Portman, Zachary M.; Arduser, Mike; Powley, Mary E.; Cariveau, Daniel P. (European Journal of Taxonomy, 2024)
The identification of females of Agapostemon angelicus Cockerell and A. texanus Cresson has been a longstanding problem, with females of the two species considered morphologically indistinguishable. Prompted by recent collections in Minnesota that unexpectedly revealed the presence of A. angelicus as well as a cryptic form of A. texanus, we reassess the taxonomy of the “doubly punctate” Agapostemon species in both Minnesota and the broader United States. Examination of both new and old specimens has allowed us to identify A. angelicus females morphologically, and we reinstate A. subtilior Cockerell stat. rev. from synonymy with A. texanus. We recognize a number of new synonyms of A. subtilior that were formerly considered synonyms of A. texanus: A. borealis Crawford syn. nov., A. californicus Crawford syn. nov., A. texanus vandykei Cockerell syn. nov., A. californicus psammobius syn. nov., A. angelicus idahoensis syn. nov., and A. californicus clementinus syn. nov. We provide keys and diagnoses to allow for morphological identification of A. angelicus, A. subtilior, and A. texanus. We show that A. texanus s. s. has a relatively restricted range in the prairie region of the United States, with A. subtilior making up the bulk of what was formerly considered A. texanus. We further show that A. angelicus has a more extensive range than previously thought. Additional work remains, as there are a number of gaps in the known ranges of these species and more taxonomic work is required in the A. texanus complex south of the United States.